Case Studies of Clinician-Guided, Online Therapy: Towards a Fuller Understanding of How and Under What Conditions Such Therapy Works - Caspar, Franz (Pragmatic Case Studies in Psychotherapy, 2017)
Ciuca, Berger, and Miclea (2017) and Schulz, Vincent, & Berger (2017) each present a pair of process-focused, systematic case studies, one with good outcome and one with a poorer outcome. These cases were drawn from a randomized controlled trial (RCT) of an Online self-help therapy for panic disorder and social anxiety disorder, respectively. In both instances the cases were drawn from the clinician-guided arm of the RCT. This commentary reviews the kind of knowledge emerging from these pairs of case studies from a variety of perspectives, including: the practical advantages of online, clinician-guided treatment; client readiness for treatment; the role of the therapist alliance; the broad reach of online therapy; and the important complementary role that systematic case studies play in enhancing the knowledge that emerges from RCTs.